The development of national qualifications frameworks in Europe - (:unkn) unknown (Publications Office of the European Union, 2010)
This second Cedefop overview on the development of national qualifications frameworks (NQFs) demonstrates the continuing progress in developing such frameworks across Europe. In total, thirty-one countries (the 27 members of the European Union, candidate countries Croatia and Turkey and European Economic Area members Iceland and Norway) are in the process of developing or implementing a national qualification framework. Beyond their technical usefulness as links between national systems of qualification to the European Qualification Framework, these tools support national reforms and lifelong learning policies. Moreover, they are instrumental in promoting the learning outcomes approach and in eroding barriers between vocational and higher education. The report pays particular attention to the relationships between the NQFs for lifelong learning (developed in response to the EQF) and the qualifications frameworks for higher education (developed in response the qualifications framework for European higher education area in the Bologna process). (BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; G 1.3.3.3 Mobilität; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 2.2 Europa; EU-Bildungspolitik; Mobilität; Nationaler Qualifikationsrahmen; Durchlässigkeit im Bildungssystem; Lebenslanges Lernen; Europäische Union; Kroatien; Türkei; Island; Norwegen